Features of classification and examination of butter and spreads - N. V. Kryvоruchkо; T. S. Kyrychenkо (Bulletin of Kharkiv National University of Internal Affairs)
Spreads are modern fat products whose production technology allows for a wide range of products with predefined properties. Having a similar texture and composition to natural butter, spreads contain more essential polyunsaturated fatty acids, and therefore exceed it in nutritional value. During the customs commodity expertise, it is important to identify the fatty product in order to provide reliable information to the consumer.